FumDSB Can Reduce the Toxic Effects of Fumonisin B1 by Regulating Several Brain-Gut Peptides in Both the Hypothalamus and Jejunum of Growing Pigs - Quancheng Liu; Fuchang Li; Libo Huang; Wenjie Chen; Zhongyuan Li; Chunyang Wang (Toxins, 2021)
Fumonisin B1 (FB1) is the most common food-borne mycotoxin produced by the Fusarium species, posing a potential threat to human and animal health. Pigs are more sensitive to FB1 ingested from feed compared to other farmed livestock. Enzymatic degradation is an ideal detoxification method that has attracted much attention. This study aimed to explore the functional characteristics of the carboxylesterase FumDSB in growing pigs from the perspective of brain–gut regulation. A total of 24 growing pigs were divided into three groups. The control group was fed a basal diet, the FB1 group was supplemented with FB1 at 5 mg/kg feed, and the FumDSB group received added FumDSB based on the diet of the FB1 group. After 35 days of animal trials, samples from the hypothalamus and jejunum were analyzed through HE staining, qRT-PCR and immunohistochemistry. The results demonstrated that the ingestion of FB1 can reduce the feed intake and weight gain of growing pigs, indicating that several appetite-related brain-gut peptides (including NPY, PYY, ghrelin and obestatin, etc.) play important roles in the anorexia response induced by FB1. After adding FumDSB as detoxifying enzymes, however, the anorexia effects of FB1 were alleviated, and the expression and distribution of the corresponding brain-gut peptides exhibited a certain degree of regulation. In conclusion, the addition of FumDSB can reduce the anorexia effects of FB1 by regulating several brain-gut peptides in both the hypothalamus and the jejunum of growing pigs.